Hospital Discharge Needs: Perspectives of Patients with Liver and Bile Duct Cancer Undergoing Invasive Percutaneous Transhepatic Biliary Drainage and Family Caregivers - Rattanakanlaya, Kanittha; Vuttanon , Nuttamon; Noppakun , Lalida; Sangwattanarat, Wantanee; Boonyu, Nongnuch (Nursing Journal CMU, 2021)
The perceived needs of patients with liver and bile duct cancer undergoing invasive percutaneous transhepatic biliary drainage and their family caregivers regarding hospital discharge readiness are essential information for discharge planning. This qualitative research aimed to describe the needs of patients and their family caregivers for hospitals’ readiness to discharge. The informants were 20 liver cancer and cholangiocarcinoma patients who underwent invasive percutaneous transhepatic biliary drainage and their family caregivers selected by a purposive sampling method. Data were collected through in-depth interviews. Thematic analysis was used. The results revealed that the hospital discharge needs of patients and their family caregivers could be classified into four themes: 1) physical readiness of patients; 2) patients’ knowledge about self-care at home and families’ knowledge about homecare for patients; 3) proper teaching about hospital discharge; and 4) homecare support. The findings of this study provide better understanding about the needs of patients and their family caregivers regarding hospital discharge. The findings can guide nurses to improve hospital discharge planning.